Continuous and patterned deposition of functional block copolymer thin films using electrospray. (9th June 2015) - Hu, Hanqiong; Toth, Kristof; Kim, Myungwoong; Gopalan, Padma; Osuji, Chinedum O.
Abstract: Abstract : We report the use of electrospray to continuously deposit thin films, including patterned films, of a block copolymer (BCP). High substrate temperatures led to vertically oriented cylindrical microdomains at the film surface independent of the solvent composition and deposition rates utilized. Conversely, low substrate temperatures resulted in morphologies that were more sensitive to these parameters, with poorly ordered films of globular structures observed at the lowest temperatures considered. The deposition pattern is defined by spatially varying the electric field at the substrate using an underlying charged grid. These results open up new possibilities for patterned deposition of BCP films with morphological control.